2013
DOI: 10.1111/tops.12008
|View full text |Cite
|
Sign up to set email alerts
|

Actively Learning Object Names Across Ambiguous Situations

Abstract: Previous research shows that people can use the co-occurrence of words and objects in ambiguous situations (i.e., containing multiple words and objects) to learn word meanings during a brief passive training period (Yu & Smith, 2007). However, learners in the world are not completely passive but can affect how their environment is structured by moving their heads, eyes, and even objects. These actions can indicate attention to a language teacher, who may then be more likely to name the attended objects. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 8 publications
(12 reference statements)
1
44
0
Order By: Relevance
“…This framework allowed us to estimate the effects of these constraints on learning to find the model that best it the data—one intermediate between the two extreme poles of parallel statistical accumulation and single-referent tracking. This unifying account provides a route by which both hypotheses and sensitivity to statistics can make complementary contributions to word learning (Waxman & Gelman, 2009; Kachergis et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…This framework allowed us to estimate the effects of these constraints on learning to find the model that best it the data—one intermediate between the two extreme poles of parallel statistical accumulation and single-referent tracking. This unifying account provides a route by which both hypotheses and sensitivity to statistics can make complementary contributions to word learning (Waxman & Gelman, 2009; Kachergis et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, participants are required to keep track of co‐occurrences between the two. Numerous studies have demonstrated that human learners are capable of tracking co‐occurring information across multiple learning trials to disambiguate between consistent and inconsistent co‐occurrences and ultimately build correct word–referent mappings (e.g., Kachergis, Yu, & Shiffrin, ; Smith, Smith, & Blythe, ; Suanda & Namy, ; Yu & Smith, ; Yurovsky, Yu, & Smith, ). This study expands upon previous research by testing whether adult learners can extract multiple levels of statistical regularities to learn object names and categories concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is commonly termed cross-situational word learning (CSWL) . Over the last 10 years, there has been significant growth in research on children’s CSWL (Scott & Fisher, 2012; Smith & Yu, 2008, 2013; Suanda, Mugwanya, & Namy, 2014; Vlach & Johnson, 2013; Vouloumanos & Werker, 2009; Yu & Smith, 2011) and adult and computational models of children’s CSWL (Fazly, Alishahi, & Stevenson, 2010; Fitneva & Christiansen, 2011; Kachergis, Yu, & Shiffrin, 2013; Medina, Snedeker, Trueswell, & Gleitman, 2011; Smith, Smith, & Blythe, 2011; Trueswell, Medina, Hafri, & Gleitman, 2013; Vlach & Sandhofer, 2014; Yu & Smith, 2007, 2012; Yurovsky & Frank, 2015; Yurovsky, Yu, & Smith, 2013). …”
mentioning
confidence: 99%